Coating composition, antistatic protective coating and preparation method
By using a coating composition with hyperbranched polysiloxane with an opposite electric starting trend, the charge amount on the surface of the material is adjusted, and an intrinsic antistatic coating with high transparency and high hardness is prepared, which solves the problem of degradation in the performance of antistatic materials in the prior art.
Patent Information
- Application Number
- CN202411857845.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-17
AI Technical Summary
When preparing antistatic protective coatings, existing antistatic materials often experience darkening of the color of the material, deteriorating optical properties and deteriorating mechanical properties, which cannot meet the needs of electronic devices and display devices for high transparency, high hardness and versatility.
An intrinsic antistatic coating is prepared by using a coating composition comprising two or more hyperbranched polysiloxanes having opposite electrical onset tendencies, by adjusting their proportion and degree of crosslinking, the amount of charge on the surface of the material is regulated.
It achieves high transparency, high hardness and good scratch resistance while meeting antistatic properties, and is suitable for coatings of different substrates and morphology.
Smart Images

Figure CN119307180B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a coating composition, an antistatic protective coating and a preparation method, and specifically relates to a coating composition for an antistatic protective coating, an intrinsic antistatic transparent protective coating prepared from the coating composition, and a related preparation method, belonging to the field of advanced coatings and preparation technology. Background Art
[0002] Static electricity is an electric charge phenomenon caused by the uneven distribution of electrons on the surface of a substance. Almost all types of materials, including metals, semiconductors, inorganic materials and polymers, are susceptible to electrification through contact, induction or friction. Large amounts of accumulated static electricity are difficult to release, which can have a significant impact on production and life. For example, in the packaging industry, static electricity may cause damage to products or dust to adhere to packaging materials; in the medical field, static electricity discharge may interfere with the normal operation of medical equipment, leading to medical accidents and endangering personal safety; in the textile industry, static electricity problems often cause fabrics to absorb dust and fibers, affecting the appearance and comfort of the fabric; and during the production and operation of electronic equipment, static electricity discharge may damage important electronic components, causing equipment damage or performance degradation. In this context, the development of materials with antistatic properties is particularly important.
[0003] There are two main strategies for preparing traditional antistatic materials: one is to add conductive fillers such as metal particles, carbon black, carbon nanotubes and ionic antistatic agents to insulating materials to increase the conductivity of the material to 10 12 ~10 6 Ω / sq; second, free radical scavengers are introduced into the material, such as 2,2-biphenyl-1-picrylhydrazyl (DPPH), 2,2,6,6-tetramethylpiperidinyl oxide and ascorbic acid, to dissipate static electricity. However, when the above strategies are used to prepare antistatic protective coatings, the color of the materials becomes darker, the optical properties decrease, and the mechanical properties deteriorate seriously, thus failing to meet the high transparency, high hardness and multifunctionality required for electronic devices and display devices. Therefore, how to achieve antistatic properties of coating materials while having high transparency, high hardness and good scratch resistance is a problem that needs to be solved urgently.
[0004] In the prior art, for example, the preparation process of an intrinsic antistatic hardened film disclosed in Chinese patent CN103642384B is to mix nano-scale conductive materials (such as carbon nanotubes, nano-ATO, graphene, etc.) with compound antistatic agents, mix them with diluents added with acrylic prepolymers, and then add silicone resins and photoinitiators in sequence, and finally cure them to obtain the intrinsic antistatic hardened film obtained by this method. The surface resistance is small, the static dissipation time is short, and the film thickness is thin, the transparency is high (the transmittance reaches 91.1%, and the haze reaches 1.1%), and the hardness (2 H or 3 H), wear resistance and toughness are improved compared with ordinary acrylic hardened films. This patent still adds conductive fillers. Although the different distribution characteristics of compound antistatic agents and nano-scale conductive materials in the hardened layer are used to achieve a better antistatic effect, the hardness of the hardened film needs to be improved, and the patent does not verify the wear resistance and toughness of the hardened film. Summary of the invention
[0005] The purpose of the present invention is to provide a coating composition, which includes two or more hyperbranched polysiloxanes with opposite charging tendencies. After the polysiloxanes are mixed and cross-linked in a specific ratio, the charge on the surface of the material can be effectively regulated, thereby preparing an intrinsic antistatic coating material, achieving the purpose of permanently reducing or even eliminating the generation of charge.
[0006] Another object of the present invention is to provide an antistatic protective coating prepared from the above-mentioned coating composition and a preparation method thereof. The antistatic protective coating prepared by the method has a transmittance of >95% (550 nm, excluding the substrate), a pencil hardness of up to 9 H (10 μm), no scratches after 1500 cycles (50 μm) of steel wool friction test, and a minimum bending radius of curvature of 1 mm (15 μm, PET substrate). Therefore, while meeting the antistatic properties of the coating, the coating has high transparency, high hardness and good scratch resistance.
[0007] The present invention is achieved through the following technical solution: a coating composition, which comprises, by weight percentage, 100 parts of a silane monomer combination, 1 to 200 parts of a catalyst, and 200 to 400 parts of a solvent.
[0008] Every 100 parts of the silane monomer combination includes 20 to 80 parts of a silane monomer that tends to generate positive electricity (potential) by friction and 20 to 80 parts of a silane monomer that tends to generate negative electricity (potential) by friction, and the silane monomer is selected from the compounds of the structural formula shown in the following formula I or formula II:
[0009]
[0010] Formula Ⅰ Formula Ⅱ
[0011] When the silane monomer is rubbed to a positive potential, the R group of the silane monomer is R + , R + Selected from , , , , , , , , or One of;
[0012] When the silane monomer is rubbed to a negative charge (potential), the R group of the silane monomer is R - , R - Selected from , , , , , or One of them.
[0013] In the silane monomer combination, the molar ratio of the silane monomer that tends to generate positive electricity (potential) by friction to the silane monomer that tends to generate negative electricity (potential) by friction is 8:2 to 2:8.
[0014] The catalyst comprises an acid catalyst or a base catalyst, wherein the acid catalyst is selected from at least one of hydrochloric acid, phosphoric acid, formic acid or glacial acetic acid; and the base catalyst is selected from at least one of ammonia water, tetramethylammonium hydroxide, triethylamine or water.
[0015] The solvent is selected from at least one of water, methanol or an aqueous solution thereof, ethanol or an aqueous solution thereof, and isopropanol or an aqueous solution thereof.
[0016] A method for preparing an antistatic protective coating using the coating composition comprises the following steps:
[0017] S1. The silane monomers are hydrolyzed in different groups according to the hydrolysis mode. During the hydrolysis, the silane monomers are dissolved in a solvent and a catalyst is added. After the hydrolysis, the solvent and the catalyst are evaporated to obtain a pre-hydrolysis product. The pre-hydrolysis products of each group are mixed and stirred to obtain a coating;
[0018] S2. Apply the coating on the base material, heat and cure it to obtain an antistatic protective coating.
[0019] The coating method is selected from one of spray coating, drop coating, blade coating, rod coating or spin coating.
[0020] The substrate material is selected from at least one of glass, ceramic, aluminum, copper, stainless steel, polycarbonate, polymethyl methacrylate, polyethylene terephthalate or polyimide.
[0021] During the heating and curing, the curing is carried out at 50 to 150° C. for 10 to 300 min.
[0022] An antistatic protective coating prepared by the above method, wherein the antistatic protective coating at least meets the following performance indicators:
[0023] Coating thickness: 2 nm~200 μm;
[0024] Transmittance: >95% at 550 nm (subtracting substrate);
[0025] Pencil hardness: 3~9 H.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] (1) In the present invention, chemical groups with strong and opposite electrification tendencies are selected in the coating composition, and the electrical properties of the coating are adjusted by adjusting the ratio to completely prevent the generation of electrostatic charges, so that the antistatic coating prepared by the present invention is independent of patterning and spatial distribution and has uniform electrical properties. At the same time, in combination with the siloxane system, high transparency and high hardness can be achieved, and the coating is suitable for different substrates and morphologies.
[0028] (2) The coating of the present invention is a thermosetting polysiloxane resin with a highly cross-linked structure, which has the dual characteristics of organic and inorganic materials. In addition, the coating has a variety of terminal groups. By selecting monomers or compositions of different types, proportions and structures, the antistatic properties, mechanical properties and surface properties of the coating can be controlled in a variety of combinations and proportions to meet the needs of different application environments.
[0029] (3) The coating provided by the present invention has simple composition, and the raw materials are all commercial products. The preparation process is simple and does not require overly complicated equipment and conditions. The coating is suitable for the surface of various materials, and the antistatic effect does not change with changes in environmental conditions, and can meet the antistatic needs in different environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the preparation of the intrinsic antistatic transparent protective coating of the present invention.
[0031] Figure 2 The infrared spectra of silane monomers, coating compositions and coatings are shown in Figures 1 and 2, wherein (A) is an infrared spectra of APTMS monomers, GPTMS monomers and the coating composition of Example 8; (B) is an infrared spectra of the coatings of Example 8, Comparative Example 9 and Comparative Example 10.
[0032] Figure 3The figures are trend graphs and linear fitting graphs of the electrostatic charge of different embodiments and comparative examples as the λ value changes, wherein (A) is a trend graph of the electrostatic charge of monolayer coatings with different λ values prepared in comparative examples 3 to 8; (B) is a trend graph of the electrostatic charge of the coatings obtained in embodiments 1 to 4 and comparative examples 1 and 2; (C) is a trend graph of the electrostatic charge of the coatings obtained in embodiments 5 to 11; (D), (E) and (F) are linear fittings of the average electrostatic charge of (A), (B) and (C) as the λ value changes trend, respectively.
[0033] Figure 4 The antistatic properties of the coating are demonstrated, wherein (A) is the demonstration of the ability of copper foil to attract PS balls before and after rubbing glass; (B) is the demonstration of the ability of copper foil to attract PS balls before and after rubbing the coating of Example 8.
[0034] Figure 5 The hydrophobic and oleophobic properties of the coating are demonstrated, wherein (A) is a demonstration of the hydrophobic and oleophobic (diiodomethane) properties of the coating of Example 8; and (B) is a demonstration of the dust-proof and self-cleaning properties of the coating of Example 8.
[0035] Figure 6 The UV-visible light transmittance test of some examples and comparative example coatings (without deducting the substrate), wherein (A) is the UV-visible light transmittance of glass and comparative example 1 to comparative example 2, and example 1 to example 4 coatings; (B) is the UV-visible light transmittance of glass and example 5 to example 11 coatings.
[0036] Figure 7 The figures in (A) are polarized micrographs of the friction area of the coating of Example 11 before and after 500 times of friction with steel wool, the friction area of the coating of Example 8 before and after 1000 times of friction with steel wool, and the friction area of the coating of Example 12 before and after 1500 times of friction with steel wool; (B) is a steel wool friction device; and (C) is a scanning electron microscope image of the friction area of the coating of Example 12.
[0037] Figure 8 The flexibility of the coating of Example 12 is demonstrated, wherein (A) is a sample display of the coating of Example 12 (PET substrate); and (B) is a display of the minimum diameter of the coating when bent inward. DETAILED DESCRIPTION
[0038] The invention objectives, technical solutions and beneficial effects of the present invention are further described in detail below.
[0039] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the claimed invention, and unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs.
[0040] The present invention aims to provide a new type of antistatic transparent protective coating, which uses polysiloxane with a highly cross-linked structure as a matrix, selects monomers based on chemical groups with strong and opposite electrification tendencies, and is prepared by a sol-gel method. Among them, the siloxane structure brings unique optical and mechanical properties of organic-inorganic hybrid structures; by combining chemical groups with different electrification tendencies, electrical neutrality is achieved on the surface of the material to achieve the purpose of antistatic; the molecular structure design of siloxane and the diversity of chemical group selection provide more functional integration options for the coating and provide conditions for practical application, and finally an intrinsic antistatic transparent protective coating suitable for different environments is prepared.
[0041] The following is a further summary of the technical solution of the present invention:
[0042] The invention provides a coating composition, which comprises 100 parts of a silane monomer combination, 1 to 200 parts of a catalyst and 200 to 400 parts of a solvent.
[0043] For the silane monomer combination of the coating composition, the combination includes an R group (R + ) positively charged silane monomer and R group (R - ) is a negatively charged silane monomer, wherein the silane monomer is selected from the compounds of the following structural formulas:
[0044]
[0045] Formula Ⅰ Formula Ⅱ
[0046] When the silane monomer is rubbed to generate positive charge (potential), its R group is R + , selected from , , , , , , , , or One of;
[0047] When the silane monomer is rubbed to generate a negative charge (potential), its R group is R - , selected from , , , , , or One of them.
[0048] It should be noted that the electrification tendency described in the present invention refers to the fact that after a material containing a certain group contacts and separates from a material containing another group, the two materials will carry positive and negative charges respectively, and the judgment is made by whether the two are more likely to be positively charged or negatively charged. For example, an amino-containing coating and a fluorine-containing coating, the amino-containing coating is more inclined to be positively charged, has a positive electrification tendency or a friction tendency to be positively charged (potential), while the fluorine-containing coating tends to be negatively charged, has a negative electrification tendency or a friction tendency to be negatively charged (potential). In addition, since the strength of the electrification intensity (or charge amount) of the group is relative, rather than absolute, it will change with the different materials in contact with it (such as the electrification intensity of the amino coating after friction with copper foil and PVC board is different), which is usually related to the test conditions and environment, and the strength of the electrification can be judged by experience and test results (such as in general, among the groups that tend to be positively charged, amino>epoxy>methyl).
[0049] For every 100 parts of the silane monomer combination, the amount of the silane monomer with a positive friction tendency is 20 to 80 parts, the amount of the silane monomer with a negative friction tendency is 20 to 80 parts, and the molar ratio of the two silane monomers is 8:2 to 2:8, including but not limited to 8:2, 6:4, 4:6, 2:8. In particular, if the same type of silane monomer contains two or more monomers, the total amount of the two types of silane monomers is still taken according to the above ratio, and the same type of silane monomers are measured as needed.
[0050] The catalyst of the coating composition can be divided into acid catalyst and alkaline catalyst according to the catalytic type. When the catalytic type is acid catalysis, the selected acid catalyst can be selected from at least one of hydrochloric acid, phosphoric acid, formic acid or glacial acetic acid; when the catalytic type is alkaline catalysis, the selected alkaline catalyst can be selected from at least one of ammonia water, tetramethylammonium hydroxide, triethylamine or water. In particular, when the catalytic type is alkaline autocatalysis, no additional catalyst is required, and only water is used as a catalyst and solvent.
[0051] The solvent of the coating composition may be selected from at least one of water, methanol or an aqueous solution thereof, ethanol or an aqueous solution thereof, and isopropanol or an aqueous solution thereof.
[0052] The present invention further provides an intrinsic antistatic transparent protective coating and a preparation method thereof based on the above coating composition. Figure 1 As shown, the specific steps of the preparation method are as follows:
[0053] First, a pre-hydrolysis product is prepared, and the silane monomers are hydrolyzed in different groups according to the hydrolysis mode. During the hydrolysis, the silane monomers are dissolved in a solvent and a catalyst is added. After a period of hydrolysis, the solvent and the catalyst are removed by rotary evaporation to obtain a pre-hydrolysis product.
[0054] Then, each group of pre-hydrolyzed products are mixed, a small amount of solvent is added to prevent gelation, and the coating is obtained after stirring and mixing.
[0055] Finally, the coating is evenly coated on the surface of the substrate by spraying, dripping, scraping, rod coating or spin coating; the coating thickness is 2 nm to 200 μm, and the intrinsic antistatic transparent protective coating is obtained after heating and curing (50 to 150 ° C, 10 to 300 min).
[0056] The specific implementation of the present invention is described below in conjunction with embodiments. Of course, the protection scope of the present invention is not limited to the following embodiments.
[0057] 1) The ratios of silane monomer combination, catalyst and solvent in the following examples are all molar ratios;
[0058] 2) The UV-visible light transmittance of the intrinsic antistatic transparent protective coating obtained in the following examples was tested by UV-3600 of Shimadzu Corporation of Japan; the pencil hardness was tested by H501 pencil hardness tester of Elecometer of Britain; the flexibility was tested by a spiral micrometer; the infrared spectrum was tested by Nicolet 6700 Fourier transform infrared spectrometer; the electrostatic charge was tested by a combination of a stepper motor and a Keithley 6514 electrometer, and the steel wool abrasion test was tested by a 339 alcohol eraser friction tester.
[0059] Embodiment 1:
[0060] 3-aminopropyltrimethoxysilane (APTMS, 80 parts) was added to ethanol (240 parts), and then water (96 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. 3,3,3-trifluoropropyltrimethoxysilane (TFTMS, 20 parts) was added to ethanol (60 parts), and then water (50 parts) and hydrochloric acid (0.6 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0061] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 90.4%, and a pencil hardness of 7 H.
[0062] Embodiment 2:
[0063] APTMS (60 parts) was added to ethanol (180 parts), and then water (72 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (40 parts) was added to ethanol (120 parts), and then water (100 parts) and hydrochloric acid (1.2 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0064] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 92.3%, and a pencil hardness of 7 H.
[0065] Embodiment 3:
[0066] APTMS (40 parts) was added to ethanol (120 parts), and then water (48 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (60 parts) was added to ethanol (180 parts), and then water (150 parts) and hydrochloric acid (1.8 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0067] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 92.7%, and a pencil hardness of 5 H.
[0068] Embodiment 4:
[0069] APTMS (20 parts) was added to ethanol (60 parts), and then water (24 parts) was added, and the mixture was hydrolyzed for 2 h. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (80 parts) was added to ethanol (240 parts), and then water (200 parts) and hydrochloric acid (2.4 parts) were added, and the mixture was hydrolyzed for 6 h. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0070] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 91.1%, and a pencil hardness of 3 H.
[0071] Embodiment 5:
[0072] APTMS (80 parts) was added to ethanol (240 parts), and then water (96 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (10 parts) and 3-glycidyloxypropyltrimethoxysilane (GPTMS, 10 parts) were added to ethanol (60 parts), and then water (50 parts) and hydrochloric acid (0.6 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0073] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 90.6%, and a pencil hardness of 9 H.
[0074] Embodiment 6:
[0075] APTMS (70 parts) was added to ethanol (210 parts), and then water (84 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (20 parts) and GPTMS (10 parts) were added to ethanol (90 parts), and then water (75 parts) and hydrochloric acid (0.9 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0076] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 90.7%, and a pencil hardness of 9 H.
[0077] Embodiment 7:
[0078] APTMS (60 parts) was added to ethanol (180 parts), and then water (72 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (30 parts) and GPTMS (10 parts) were added to ethanol (120 parts), and then water (100 parts) and hydrochloric acid (1.2 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0079] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 91.1%, and a pencil hardness of 9 H.
[0080] Embodiment 8:
[0081] APTMS (50 parts) was added to ethanol (150 parts), and then water (60 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (40 parts) and GPTMS (10 parts) were added to ethanol (150 parts), and then water (125 parts) and hydrochloric acid (1.5 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0082] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 91.0%, and a pencil hardness of 9 H.
[0083] Embodiment 9:
[0084] APTMS (40 parts) was added to ethanol (120 parts), and then water (48 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (50 parts) and GPTMS (10 parts) were added to ethanol (180 parts), and then water (150 parts) and hydrochloric acid (1.8 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0085] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 90.3%, and a pencil hardness of 9 H.
[0086] Embodiment 10:
[0087] APTMS (30 parts) was added to ethanol (90 parts), and then water (36 parts) was added, and the mixture was hydrolyzed for 2 h. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (60 parts) and GPTMS (10 parts) were added to ethanol (210 parts), and then water (175 parts) and hydrochloric acid (2.1 parts) were added, and the mixture was hydrolyzed for 6 h. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0088] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 91.2%, and a pencil hardness of 9 H.
[0089] Embodiment 11:
[0090] APTMS (20 parts) was added to ethanol (60 parts), and then water (24 parts) was added, and the mixture was hydrolyzed for 2 h. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (70 parts) and GPTMS (10 parts) were added to ethanol (240 parts), and then water (200 parts) and hydrochloric acid (2.4 parts) were added, and the mixture was hydrolyzed for 6 h. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0091] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 90.5%, and a pencil hardness of 9 H.
[0092] Embodiment 12:
[0093] APTMS (50 parts) was added to ethanol (150 parts), and then water (60 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (40 parts) and GPTMS (10 parts) were added to ethanol (150 parts), and then water (125 parts) and hydrochloric acid (1.5 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0094] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then coated on a flexible substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 10 μm, a transmittance of 90.3%, and a pencil hardness of 4 H.
[0095] Comparative Example 1:
[0096] APTMS (100 parts) was added to ethanol (300 parts), and then water (120 parts) was added, and hydrolysis was carried out for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product, and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition. The solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 hours to obtain a coating material with a thickness of 30 μm, a transmittance of 90.4%, and a pencil hardness of 6 H.
[0097] Comparative Example 2:
[0098] TFTMS (100 parts) was added to ethanol (300 parts), and then water (250 parts) and hydrochloric acid (3 parts) were added, and hydrolysis was carried out for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product, and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 hours to obtain a coating material with a thickness of 30 μm, a transmittance of 91.2%, and a pencil hardness of 5 H.
[0099] Comparative Example 3:
[0100] APTMS (100 parts) was added to anhydrous toluene (200 mL) and stirred evenly. Then, the glass slide with surface hydroxylation was immersed in it for 3 h. After being taken out, the solvent was blown dry in a nitrogen flow and cured at 40 °C for 4 h to obtain a monolayer coating material.
[0101] Comparative Example 4:
[0102] APTMS (80 parts) and TFTMS (20 parts) were added to anhydrous toluene (200 mL) and stirred evenly. Then, a glass slide with surface hydroxylation was immersed in it for 3 h. After being taken out, the solvent was blown dry in a nitrogen flow and cured at 40 °C for 4 h to obtain a monolayer coating material.
[0103] Comparative Example 5:
[0104] APTMS (60 parts) and TFTMS (40 parts) were added to anhydrous toluene (200 mL) and stirred evenly. Then, a glass slide with surface hydroxylation was immersed in it for 3 h. After being taken out, the solvent was blown dry in a nitrogen flow and cured at 40 °C for 4 h to obtain a monolayer coating material.
[0105] Comparative Example 6:
[0106] APTMS (40 parts) and TFTMS (60 parts) were added to anhydrous toluene (200 mL) and stirred evenly. Then, a glass slide with surface hydroxylation was immersed in it for 3 h. After being taken out, the solvent was blown dry in a nitrogen flow and cured at 40 °C for 4 h to obtain a monolayer coating material.
[0107] Comparative Example 7:
[0108] APTMS (20 parts) and TFTMS (80 parts) were added to anhydrous toluene (200 mL) and stirred evenly. Then, a glass slide with surface hydroxylation was immersed in it for 3 h. After being taken out, the solvent was blown dry in a nitrogen flow and cured at 40 °C for 4 h to obtain a monolayer coating material.
[0109] Comparative Example 8:
[0110] TFTMS (100 parts) was added to anhydrous toluene (200 mL) and stirred evenly. Then, the glass slide with surface hydroxylation was immersed in it for 3 h. After being taken out, the solvent was blown dry in a nitrogen flow and cured at 40 °C for 4 h to obtain a monolayer coating material.
[0111] Comparative Example 9:
[0112] APTMS (55 parts) was added to ethanol (165 parts), and then water (66 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (40 parts) and GPTMS (5 parts) were added to ethanol (135 parts), and then water (113 parts) and hydrochloric acid (1.4 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0113] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 90.2%, and a pencil hardness of 7 H.
[0114] Comparative Example 10:
[0115] APTMS (30 parts) was added to ethanol (90 parts), and then water (36 parts) was added, and the mixture was hydrolyzed for 2 h. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (40 parts) and GPTMS (30 parts) were added to ethanol (210 parts), and then water (175 parts) and hydrochloric acid (2.1 parts) were added, and the mixture was hydrolyzed for 6 h. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0116] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 70 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 30 μm, a transmittance of 90.7%, and a pencil hardness of 9 H.
[0117] Comparative Example 11:
[0118] APTMS (50 parts) was added to ethanol (150 parts), and then water (60 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (40 parts) and GPTMS (10 parts) were added to ethanol (150 parts), and then water (125 parts) and hydrochloric acid (1.5 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0119] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 20 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 10 μm, a transmittance of 91.0%, and a pencil hardness of 8 H.
[0120] Comparative Example 12:
[0121] APTMS (50 parts) was added to ethanol (150 parts), and then water (60 parts) was added, and the mixture was hydrolyzed for 2 hours. Water and ethanol were removed by rotary evaporation to obtain a pre-hydrolysis product. TFTMS (40 parts) and GPTMS (10 parts) were added to ethanol (150 parts), and then water (125 parts) and hydrochloric acid (1.5 parts) were added, and the mixture was hydrolyzed for 6 hours. Water, ethanol and hydrochloric acid were removed by rotary evaporation to obtain a pre-hydrolysis product.
[0122] The two pre-hydrolysis products were mixed and ethanol was added to prepare a 90 wt% ethanol solution to obtain a coating composition; the solution was then drop-coated on a substrate, and after the solvent evaporated, it was cured at 100 °C for 4 h to obtain a coating material with a thickness of 50 μm, a transmittance of 90.4%, and a pencil hardness of 9 H.
[0123] Table 1 below shows the coating performance test results of Examples 1 to 12 and Comparative Examples 1 to 12.
[0124] Table 1 Test results of coating properties of various embodiments and comparative examples
[0125]
[0126] Note: The number of steel wool friction cycles (cycles) "—" indicates that it is not necessary to test all samples with λ values, and only representative samples in the same group are tested; thickness "—" indicates that the thickness of the monolayer coating sample does not need to be tested; transmittance "—" indicates that the transmittance of the monolayer coating sample does not need to be tested; pencil hardness "—" indicates that the pencil hardness of the monolayer coating sample does not need to be tested. In addition, the examples and comparative examples shown in Table 1 are all test data for coating substrates of glass, and the coating substrate of Example 12 is PET, which is only used to show that the coating has the potential to be applied on flexible substrates; Comparative Examples 3, 4, 7, and 8 are monolayer coating control samples with different λ values in the same group as Comparative Examples 5 and 6, and are only used to test the electrification trend of monolayer coating samples. Therefore, Table 1 does not include the test data of Example 12, Comparative Example 3, Comparative Example 4, Comparative Example 7, and Comparative Example 8.
[0127] Further, by analyzing the above embodiments and comparative examples, it can be seen that:
[0128] 1) The components of the coating composition of the present invention can be successfully prepared into a coating.
[0129] See also Figure 2 As shown, Figure 2 (A) is the infrared spectrum of the silane monomer and the coating composition prepared in Example 8. It can be seen from the figure that the spectrum of the APTMS monomer and the coating composition of Example 8 is at 1600 cm -1 The NH peak appeared near 910 cm-1. The spectra of the GPTMS monomer and the coating composition of Example 8 also showed a peak at 910 cm-1. -1 The COC peak near 1270cm- 1 The nearby CF peak appears only in the spectrum of the coating composition of Example 8.
[0130] Figure 2 (B) is the infrared spectra of the coatings prepared in Example 8, Comparative Example 9 and Comparative Document 10. It can be seen from the figure that these three peaks appear in Example 8, Comparative Example 9 and Comparative Example 10, and the NH peak intensity decreases with the increase of GPTMS monomer, which proves the composition of the coating composition and the successful preparation of the coating.
[0131] 2) The coating of the present invention has antistatic properties.
[0132] The coatings prepared in Examples 1 to 11 and Comparative Examples 1 to 8 were subjected to electrostatic charge tests. The number and frequency of collisions between the coating and the collision plate material were controlled by a stepper motor, and the electrostatic charge information was collected by an electrometer.
[0133] The results show that monolayer coatings with different λ values were prepared from Comparative Examples 3 to 8. Figure 3 (A), silicone resin coatings with different λ values were prepared from Examples 1 to 4 and Comparative Examples 1 to 2, and Examples 5 to 11, and their electrostatic charge values showed the same trend as the λ value changes, see Figure 3 (B) and Figure 3 (C); When λ reaches a certain critical value, the coating can achieve the effect of no electrification. At this time, λ is the "zero electrification point", see Figure 3 (D)~ Figure 3 (F).
[0134] Furthermore, the coating prepared in Example 8 was subjected to antistatic demonstration. After rubbing the glass and the coating in Example 8 with copper foil, they were placed in a beaker filled with PS balls. The glass attracted a large number of PS balls to adhere to the surface due to frictional electrification. Figure 4 (A); while the coating of Example 8 hardly attracts small balls after friction, see Figure 4 (B), thus demonstrating the antistatic effect of the coating.
[0135] 3) The coating of the present invention has hydrophobic and oleophobic capabilities.
[0136] See also Figure 5 As shown in (A), water and diiodomethane (C2I2) were added dropwise onto the coating of Example 8, and the droplets quickly slid off the coating without leaving any traces, which proved the hydrophobic and oleophobic ability of the coating; see Figure 5 As shown in (B), the coating surface of Example 8 is covered with dust. When the glass is tilted at a small angle, the dust can be easily removed from the coating surface by washing with water droplets.
[0137] 4) The coating of the present invention has good light transmittance.
[0138] See also Figure 6 As shown, without deducting the glass substrate (glass transmittance 89.7%), the transmittance of the coatings of Examples 1 to 12 and Comparative Examples 1 and 2 is all greater than 90% (550 nm, without deducting the substrate); in particular, taking Example 8 as an example, after deducting the background of the glass substrate, the transmittance of the coating of Example 8 at 550 nm is 99.1%, which proves that the coating prepared by the present invention has high transmittance and the coating does not affect the transmittance of the substrate.
[0139] 5) The coating of the present invention has good wear resistance.
[0140] See also Figure 7 As shown, the coatings prepared in Comparative Example 11, Example 8, and Comparative Example 12 were subjected to a steel wool friction test (1500 times, 130 kPa), and the wear resistance of the coatings increased with increasing thickness. Figure 7 (A) The upper picture is before the test. Figure 7 The lower figure in (A) shows the corresponding coating after testing; the coating thickness of comparative example 12 is 50 μm and can withstand 1500 frictions without scratches, see Figure 7 (A) middle right; Figure 7 (C) is a SEM image of the surface of the coating of comparative example 12 after friction, and no scratches are found, which proves that the coating has good wear resistance.
[0141] 6) The coating of the present invention has a certain flexibility.
[0142] See also Figure 8 As shown, the coating composition of Example 12 was coated on the surface of PET (30 μm), and the coating had a high transmittance of 90.3% (without deducting the PET substrate), see Figure 8 (A), the pencil hardness can also reach 4 H, and its bending radius is 1 mm, see Figure 8 (B) This demonstrates that the coating has a certain degree of flexibility and has the potential to be used in flexible devices.
[0143] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A highly transparent flexible antistatic protective coating, characterized in that: The antistatic protective coating is prepared by combining coating prepolymers. The coating composition comprises 100 parts of a silane monomer combination, 1 to 200 parts of a catalyst and 200 to 400 parts of a solvent, and each 100 parts of the silane monomer combination contains at least three or more silane monomers, including 20 to 80 parts of a silane monomer that tends to be positively charged by friction and 20 to 80 parts of a silane monomer that tends to be negatively charged by friction, and the silane combination contains at least a silane that can react with the silane monomer that tends to be positively charged by friction, and the silane monomer is selected from the compounds of the structural formula shown in the following formula I or formula II: Formula Ⅰ Formula Ⅱ When the silane monomer is rubbed to be positively charged, the R group of the silane monomer is R+, and R+ is selected from , , , , or One of When the silane monomer is rubbed, it tends to be negatively charged. The R group of the silane monomer is R-, and R- is selected from , , , or The catalyst comprises an acid catalyst or a base catalyst, the acid catalyst is selected from at least one of hydrochloric acid, phosphoric acid, formic acid or glacial acetic acid; the base catalyst is selected from at least one of ammonia water, tetramethylammonium hydroxide, triethylamine or water; The antistatic protective coating at least meets the following performance indicators: Coating thickness: 2 nm~200 μm; Transmittance: >95% at 550 nm; Pencil hardness: 3~9 H.
2. The highly transparent flexible antistatic protective coating according to claim 1, characterized in that: In the silane monomer combination, the molar ratio of the silane monomer that tends to generate positive charge by friction to the silane monomer that tends to generate negative charge by friction is 8:2 to 2:
8.
3. The highly transparent flexible antistatic protective coating according to claim 1, characterized in that: The solvent is selected from at least one of water, methanol or an aqueous solution thereof, ethanol or an aqueous solution thereof, and isopropanol or an aqueous solution thereof.
4. A method for preparing the highly transparent flexible antistatic protective coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. The silane monomers are hydrolyzed in different groups according to the hydrolysis mode. During the hydrolysis, the silane monomers that tend to be positively charged by friction are added to a solvent to be dissolved and a catalyst is added. After the hydrolysis, the solvent and the catalyst are evaporated to remove the solvent and the catalyst to obtain a group of pre-hydrolysis products. The silane monomers that tend to be negatively charged by friction and the silane that can react with the silane monomers that tend to be positively charged by friction are added to a solvent to be dissolved and a catalyst is added. After the hydrolysis, the solvent and the catalyst are evaporated to remove the solvent and the catalyst to obtain another group of pre-hydrolysis products. After the pre-hydrolysis products of each group are mixed and stirred evenly, a coating is obtained. S2. Apply the coating on the base material, heat and cure it to obtain an antistatic protective coating.
5. The method according to claim 4, characterized in that: The coating method is selected from one of spray coating, drop coating, blade coating, rod coating or spin coating.
6. The method according to claim 4, characterized in that: The substrate material is selected from at least one of glass, ceramic, aluminum, copper, stainless steel, polycarbonate, polymethyl methacrylate, polyethylene terephthalate or polyimide.
7. The method according to claim 4, characterized in that: During the heating and curing, the curing is carried out at 50 to 150° C. for 10 to 300 min.
Citation Information
Patent Citations
A kind of intrinsic type antistatic hardening film and preparation method thereof
CN103642384B
Anti-reflective and anti-soiling coatings with self-cleaning properties
CN103917503A
Anti-static coating material and preparation method thereof as well as anti-static coating and generation method thereof
CN118978860A